Surgical treatment of congenital aural atresia – is it still justified?. (March 2014) - Edfeldt, Lennart; Strömbäck, Karin
Abstract Conclusion: Surgery candidacy based on the surgical accessibility of the middle ear seems more valuable than the use of a preoperative grading system. Also patients with severe malformations can benefit from surgical reconstruction. Objective: To evaluate the long-term results of the primary surgical treatment of patients with congenital auricular atresia (CAA). Methods: One hundred patients with CAA underwent surgical reconstruction between 1985 and 2010. The mean follow-up time was 40 months. All patients were retrospectively scored using the Jahrsdoerfer grading scale and divided into two groups according to the grade of their malformation. Group 1 included 20 patients with scores of 4–6 and group 2 included 80 patients with scores of 7–10. Pre- and postoperative air conduction (AC), bone conduction (BC), pure-tone average 'air–bone gap' (PTA4-ABG), surgical findings, postoperative complications, and revision surgeries performed were determined and compared between the two groups. Results: For 90% of the patients in group 1 and 79% of the patients in group 2, the postoperative ABG was within 0 and 30 dB. The most common complications were recurrent infection, lateralization of the tympanic membrane, and restenosis of the ear canal.